#### Answer

The answer is $(2\sqrt6-2\sqrt11)\div5$

#### Work Step by Step

We can simplify the expression as follows:
$= -2\div(\sqrt6+\sqrt11)$
$= -2\div(\sqrt6+\sqrt11)*(\sqrt6-\sqrt11)\div(\sqrt6-\sqrt11)$
(It is always preferred to keep the denominator after simplifying the radicals, so multiply and divide by $(\sqrt6-\sqrt11)$)
$= -2*(\sqrt6-\sqrt11)\div(\sqrt6)^{2}-(\sqrt11)^{2}$
(Since $(a+b)(a-b)=a^{2}-b^{2}$)
$= -2\sqrt6+2\sqrt11\div(6-11)$
$= -2\sqrt6+2\sqrt11\div(-5)$
$= (2\sqrt6-2\sqrt11)\div5$
(Multiply and divide by -1)